BEYOND FORGETTING: APPLYING INFORMATION PROCESSING THEORY TO ENHANCE ENGLISH LANGUAGE LEARNING ENGAGEMENT IN CHILDREN WITH NEUROCOGNITIVE IMPAIRMENT - Etika, Indah; Suhaili, Neviyarni (Sekolah Tinggi Bahasa Asing Prayoga Padang, 2025)
Children struggling with neurocognitive impairment frequently experience limitations in attention, working memory, and information retrieval. These conditions contribute to low learning engagement and difficulty retaining material in learning English as a Foreign Language (EFL) within inclusive classroom settings. This conceptual review applies Information Processing Theory (Atkinson & Shiffrin, 1968; Baddeley, 2017) to examine these cognitive challenges through three core stages: encoding, storage, and retrieval. Using a descriptive-qualitative approach, the study reviews 20 sources published predominantly between 2015 and 2025, comprising Scopus-indexed international research and relevant Indonesian studies. The synthesis identifies practical EFL strategies that can support students with neurocognitive impairment: (1) multisensory input combined with schema activation to strengthen encoding; (2) chunking paired with spaced repetition to improve storage and consolidation; and (3) retrieval practice using children’s songs with missing lyrics and pictures and pragmatic contexts to boost retrieval and engagement. These strategies are feasible for inclusive settings. The review highlights the need for empirical intervention studies and targeted teacher training to effectively bridge cognitive psychology and inclusive EFL education